2005
DOI: 10.1007/s10815-005-7482-x
|View full text |Cite
|
Sign up to set email alerts
|

The “Spanning Protocol”: A new DNA extraction method for efficient single-cell genetic diagnosis

Abstract: The spanning protocol was most efficient for extracting DNA from a single cell and should be particularly useful for preimplantation genetic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…NL ( N -Lauroylsarcosine salt) method: this method was performed as described before with modifications [13]. Briefly, the cells were suspended in 15 μl lysis buffer (3 μl H 2 O, 3 μl 250 ng/μl polyadenylic acid, 3 μl 10 mM EDTA, 3 μl 250 mM DTT, 3 μl 0.5% N -Lauroylsarcosine salt solution); followed by incubation at 95°C for 10 min; the supernatant was used for PCR directly after centrifugation at 12,000 rpm for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…NL ( N -Lauroylsarcosine salt) method: this method was performed as described before with modifications [13]. Briefly, the cells were suspended in 15 μl lysis buffer (3 μl H 2 O, 3 μl 250 ng/μl polyadenylic acid, 3 μl 10 mM EDTA, 3 μl 250 mM DTT, 3 μl 0.5% N -Lauroylsarcosine salt solution); followed by incubation at 95°C for 10 min; the supernatant was used for PCR directly after centrifugation at 12,000 rpm for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…For the Proteinase K/SDS lysis buffer method, the cell was placed in 3 mL lysis buffer (1 mL of 17 mM SDS and 2 mL of 125 mg/ml proteinase K), centrifuged, and incubated for 60 minutes at 37 C followed by 15 minutes at 95 C (21). Finally, for the N-lauroylsarcosine salt solution method, the cell was placed in a PCR tube containing 10 mL of DNA lysis buffer composed of H 2 O (2 mL), 250 ng/mL polyadenylic acid (2 mL), 10 mM EDTA (2 mL), 250 mM dithiothreitol solution (2 mL), and 0.5% N-lauroylsarcosine salt solution (2 mL), and stored at À20 C until the PCR assays were performed (16).…”
Section: Extraction Of Dna From a Single Cellmentioning
confidence: 99%
“…It depends on the cell type analyzed (11), the genes tested (12), the lysis conditions (13,14), as well as the PCR conditions (15). Tsuchiya et al (16) have recently developed a new DNA extraction method, called the ''Spanning protocol.'' These investigators reported that their spanning protocol decreases the incidence of amplification failure, as well as the rate of false-negatives.…”
mentioning
confidence: 99%
“…For isolation of single lymphocytes, an aliquot of the cell suspension was thawed and 1 µl was added to 4 ml of 90% RPMI1640 supplemented with 10% FCS in a culture plate. Individual lymphocytes were deposited in 4 µl of lysis solution 1 (0.2% sarcosyl, TE containing 10 mM EDTA) [23], with a mouth-controlled glass microcapillary under an inverted microscope. The cells were then denatured at 65 • C for 10 min and kept frozen at −20 • C until the PCR procedure.…”
Section: Sampling Of Single Lymphocytesmentioning
confidence: 99%